Generic Explanations for Generics - Ralston, Tom (Proceedings of the Amsterdam Colloquium, 2024)
It is widely accepted that generics express law-like generalisations, on the basis of evidence that their truth does not depend only on how things are in the actual world at one moment in time. In this paper, I propose a temporal truthmaker semantics for generics and argue that this theory can account for the intuition that generics express law-like generalisations. The law-likeness of generics therefore does not motivate the introduction of either the unarticulated constituent ‘GEN’ or a domain of abstract kinds. Instead, it can be explained by the nature of the states which make generics true, which may be either generic facts about a category, or particular facts about the instances of a category.